Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Andri, Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this study was to determine the effect of profitability, liquidity, growth on assets, and investment opportunity set on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period 2015 - 2017. The sampling method used was purposive sampling with the total sample is 162 data which was financial statements and performance report. The collected data were analyzed by using IBM SPSS application program. The results showed that the independent variable was able to explain the dependent variable by 97%, while the other 3% was explained by other variables that were not examined. The independent variables of profitability and investment opportunity set have a significant influence on firm value, while the independent variables of liquidity and growth on assets have a not significant effect on firm value.